Three Huntington's Disease Specific Mutation-Carrying Human Embryonic Stem Cell Lines Have Stable Number of CAG Repeats upon In Vitro Differentiation into Cardiomyocytes. - Laureen Jacquet; Andreas Neueder; Gabor Földes; Panagiotis Karagiannis; Carl Hobbs; Nelly Jolinon; Maxime Mioulane; Takao Sakai; Sian E Harding; Dusko Ilic (PLoS ONE)
Huntington disease (HD; OMIM 143100), a progressive neurodegenerative disorder, is caused by an expanded trinucleotide CAG (polyQ) motif in the HTT gene. Cardiovascular symptoms, often present in early stage HD patients, are, in general, ascribed to dysautonomia. However, cardio-specific expression of polyQ peptides caused pathological response in murine models, suggesting the presence of a nervous system-independent heart phenotype in HD patients. A positive correlation between the CAG repeat size and severity of symptoms observed in HD patients has also been observed in in vitro HD cellular models. Here, we test the suitability of human embryonic stem cell (hESC) lines carrying HD-specific mutation as in vitro models for understanding molecular mechanisms of cardiac pathology seen in HD patients. We have differentiated three HD-hESC lines into cardiomyocytes and investigated CAG stability up to 60 days after starting differentiation. To assess CAG stability in other tissues, the lines were also subjected to in vivo differentiation into teratomas for 10 weeks. Neither directed differentiation into cardiomyocytes in vitro nor in vivo differentiation into teratomas, rich in immature neuronal tissue, led to an increase in the number of CAG repeats. Although the CAG stability might be cell line-dependent, induced pluripotent stem cells generated from patients with larger numbers of CAG repeats could have an advantage as a research tool for understanding cardiac symptoms of HD patients.